How corporate cultures coevolve with the business environment: the case of firm growth crises and industry evolution - Cordes, Christian; Richerson, Peter J.; Schwesinger, Georg (Papers on economics and evolution, 2009)
This paper shows how cognitive human dispositions that take effect at the level of an individual firm’s corporate culture have repercussions on an industry's evolution. In our theory, the latter is attributable to evolving corporate cultures coupled with changes in a firm's business environment. With the help of a formal model of evolving corporate cultures, we demonstrate how firms can establish a cooperative cultural regime that yields competitive advantages in an innovative, fast changing environment. Depending on within-firm social learning processes and cognitive constraints of human agents, organizations then reach a critical cognitive firm size in their development beyond which the level of cooperation deteriorates rapidly they systematically face a growth crisis. Organizations successful in such an environment and reaching a critical technological size may, however, reap economies of scale in a later, mature and stable business environment with altered corporate culture. Furthermore, we relate these findings to empirical evidence on firm survival and performance in different industries, the evolution of organizational structures, technological advancements in production technologies, and identify some determinants of market structures. -- Industry Evolution ; Critical Firm Sizes ; Firm Growth ; Corporate Culture ; Human Cognition
Keywords: Arbeitspapier; Graue Literatur